Diagnóstico del estado actual de bienes inmuebles antiguos y privados desde 1950 hasta 2017 en la ciudad de Riobamba. - Espinoza Vaca, Edgar Santiago (2018)
This research carried out a current state diagnostic about private and ancient real estate assets from 1950 to 2017 within the city of Riobamba. In essence, some civil engineers, architects and restores. Some criteria to develop a methodology were taken into account which consisted on the development of cards. They allowed classifying assets into case studies in order to determine their architectural and structural typologies; additionally, it served as a booklet to suggest appropriate techniques for the rehabilitation of the ancient real estate assets. At the end of the investigation, a diagnostic tool was obtained which established the main evaluation parameters such as materials, pathologies, state of conservation of the structure, analysis of seismic vulnerability and a recommended technique. The diagnostic tool is feasible within several disciplines for future rehabilitation of old buildings. In the particular case of the Riobamba city, the limited control over the preservation and use historic spaces have contributed to growing commercialization and administrative centralization that has created a lack of interest to preserve ancient old buildings, and allow a modern building progressive development. Therefore, it alters some historical character of this area by limiting rehabilitation work.